СОВЕТ ҲУКУМАТИ ТОМОНИДАН ЎЗБЕКИСТОН ССР ҚИШЛОҚ ХЎЖАЛИГИ СОҲАСИДАГИ ИЛМИЙ ТАДҚИҚОТ ВАЗИФАЛАРИНИ ҲАЛ ҚИЛИШ МАСАЛАСИ ТЎҒРИСИДА - Бахранов Ш. Т. (TARIXIY TADQIQOTLAR, 2026)
This article is devoted to the policy of the Soviet authorities within the framework of research tasks in the field of agriculture in the Uzbek SSR. The study analyzes the activities of the Cotton Research Institute, in particular its role in coordinating and directing scientific research in the sphere of cotton growing. The research substantiates that the institute contributed to the increase of cotton production, improvement of its quality, and the introduction of new technologies in cotton cultivation. The article also examines the problems related to the activities of research institutes and organizations dealing with personnel issues; it is also proven that the Soviet authorities systematically interfered in the work of research institutes and other associations, which had a negative impact on the functioning of these organizations.